UNIFORMLY ACCELERATED FINITE-TIME DETECTORS - Higuchi, A.; Matsas, GEA; Peres, C. B. (American Physical Soc, 1993)
The behavior of uniformly accelerated detectors in the Minkowski and Rindler vacua is analyzed when the detector is coupled to a scalar field during a finite amount of time T. We point out that the logarithmic ultraviolet divergences reported in the literature are due to the instantaneous switching of the detector. We explicitly show this by considering a detector switched on and off continuously. The usual Planckian spectrum for the excitation probability is recovered in the limit T --> infinity.